PENGARUH MODAL SENDIRI DAN JUMLAH ANGGOTA TERHADAP SISA HASIL USAHA PADA KOPERASI DI KECAMATAN SEBERIDA KABUPATEN INDRAGIRI HULU - Riska Ismawanti; Mariaty Ibrahim (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
This study aims to determine the Effect of Own Capital and Number of Members Against Time Remaining Products at the Cooperative Unit of Koperasi Kecamatan Seberida Kabupaten Indragiri Hulu. The method used in measuring own capital is the capital owned by the company sourced from mandatory savings, principal savings and reserve funds. The number of members is obtained from the large number of members in the cooperative. The remaining results of cooperative operations are income of cooperatives obtained in one year, reduced by depreciation and costs from the relevant financial year or commonly referred to as net income. The method used to observe the effect of own capital and the number of members on financial performance is by using simple linear regression and multiple linear regression.The data used in this study are primary data and secondary data, namely cooperative field research and reports on the annual meeting of the Koperasi Kecamatan Seberida Kabupaten Indragiri Hulu. The data used are the annual cooperative member meeting report data from 2009 to 2018. Data analysis uses simple linear regression analysis, multiple linear regression, t test and f test.The results of the analysis show that the equity variables have no significant effect on the remaining results of the cooperative effort partially. The variable number of members also has no significant effect on the remaining results of the cooperative effort partially. Then, the variable own capital and number of members also did not have a significant effect on the remaining results of the operations of the Cooperative Unit of the Koperasi Kecamatan Seberida Kabupaten Indragiri Hulu. Keywords: own capital, number of members, remaining results of operation